2012
DOI: 10.1155/2012/169170
|View full text |Cite
|
Sign up to set email alerts
|

MAP Kinases and Prostate Cancer

Abstract: The three major mitogen-activated protein kinases (MAPKs) p38, JNK, and ERK are signal transducers involved in a broad range of cell functions including survival, apoptosis, and cell differentiation. Whereas JNK and p38 have been generally linked to cell death and tumor suppression, ERK plays a prominent role in cell survival and tumor promotion, in response to a broad range of stimuli such as cytokines, growth factors, ultraviolet radiation, hypoxia, or pharmacological compounds. However, there is a growing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 118 publications
1
61
0
3
Order By: Relevance
“…Of relevance to the present study, a PDX model of PC devoid of AR signaling was shown to express high levels of FGF9, which promoted tumor growth, induced an osteoblastic tumor microenvironment, and responded to FGF-directed therapy (Li et al, 2008). MAPK signaling promotes poorly differentiated tumor growth in models of PC (Mulholland et al, 2012), and constitutive ERK1/2 activity is associated with castration resistance (Gioeli et al, 1999; Oka et al, 2005; Rodriguez-Berriguete et al, 2012). While there is evidence suggesting that MAPK can stimulate ligand-independent AR activity (Feldman and Feldman, 2001), FGF/MAPK signaling did not promote the re-expression of AR-regulated genes in our models and FGFR activity was inversely associated with the expression and activity of AR in CRPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to the present study, a PDX model of PC devoid of AR signaling was shown to express high levels of FGF9, which promoted tumor growth, induced an osteoblastic tumor microenvironment, and responded to FGF-directed therapy (Li et al, 2008). MAPK signaling promotes poorly differentiated tumor growth in models of PC (Mulholland et al, 2012), and constitutive ERK1/2 activity is associated with castration resistance (Gioeli et al, 1999; Oka et al, 2005; Rodriguez-Berriguete et al, 2012). While there is evidence suggesting that MAPK can stimulate ligand-independent AR activity (Feldman and Feldman, 2001), FGF/MAPK signaling did not promote the re-expression of AR-regulated genes in our models and FGFR activity was inversely associated with the expression and activity of AR in CRPCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, generally, it appears that many if not most TKIs inhibit signaling downstream of growth factor receptors mediated by the PI3K-AKT and Ras-Raf-MEK-ERK pathways [15,16]. Activation of both the ERK and AKT pathways are a frequent event in prostate cancers and a strong association between the expression of these kinases and poor prognosis is often observed [17,18]. Thus, we tested whether sunitinib suppressed p-AKT and/or p-ERK, 2 appropriate downstream elements of the signaling pathways under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 main members that integrate the MAPK family in mammalian cells are stress-activated protein kinase c-Jun NH2-terminal kinase (JNK), stress-activated protein kinase 2 (SAPK2, p38) and the extracellular signal-regulated protein kinases (ERK1/2, p44/p42) (33). MAPK p38 has been shown to be activated by cellular stress, UV radiation, growth factor withdrawal and pro-inflammatory cytokines (34).…”
Section: Discussionmentioning
confidence: 99%